Outcomes of urinary tract abnormalities diagnosed by the routine third trimester scan. (July 2020) - Bakalis, Spyros; Cao, Kevin; Graham, Radha; Cuckow, Peter; Johal, Nav; Winyard, Paul; Pandya, Pranav; Desai, Divyesh
Abstract: Objective: The aim of this study is to determine the incidence of congenital abnormalities of the kidneys and urinary tract (CAKUT) detected for the first time in an unselected population undergoing a routine third trimester scan between 30–34 week's gestation. Methods: This was a retrospective analysis of 8562 routine third trimester ultrasound scans during which the fetal anatomy was evaluated, and, any structural abnormalities detected, recorded onto a fetal database which was subsequently analysed for CAKUT. All postnatal records of antenatally diagnosed CAKUT were obtained and analysed for diagnosis and management. Results: There were 26 cases of urological abnormalities detected for the first time in the third trimester. The most frequent abnormality was unilateral renal pelvis dilatation (73%). Postnatal ultrasound confirmed abnormalities in 19 (73%) newborns, with two (8%) resolving antenatally and four (15%) postnatally. The overall incidence of new CAKUT detected by the third trimester scan was 0.22% (19/8562) with a male to female ratio of 1:1.6. Four patients required surgery, two received cystoscopic injection of Deflux with circumcision, one received cystoscopic valve ablation and one patient received a staged hypospadias repair. Conclusion: Routine third trimester scanning is already performed in many countries with proposed benefits primarily directed towards the monitoring of fetal growth and late pregnancy malpresentation. For healthcare systems that still utilize two routine scans, debate is ongoing as to the value of introducing a routine third trimester scan. The ability to detect additional and potentially missed CAKUT is a further benefit, which in isolation is likely of too small an impact to merit implementation. However, the combination of fetal structural assessment, growth velocity monitoring and fetal presentation evaluation presents a strong case for inclusion in an antenatal screening program. The findings of this study highlight the importance of a detailed fetal structural evaluation at each antenatal ultrasound scan.